2005
DOI: 10.1001/archinte.165.16.1842
|View full text |Cite
|
Sign up to set email alerts
|

Posthospital Medication Discrepancies

Abstract: A significant percentage of older patients experienced medication discrepancies after making the transition from hospital to home. Both patient-associated and system-associated solutions may be needed to ensure medication safety during this vulnerable period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
200
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 604 publications
(213 citation statements)
references
References 35 publications
8
200
4
1
Order By: Relevance
“…The new way to think about the healthcare environment must go beyond the brick and mortar of acute care facilities. In fact, research shows that an effective formalized transition of care program should not stop at discharge [7][8][9][10][11][12] . If the patient is discharged home and falls within the high risk of readmission category, then specific steps should be in place to help to ensure that the patient undergoes a safe transition of care back into the home.…”
Section: Buildingmentioning
confidence: 99%
“…The new way to think about the healthcare environment must go beyond the brick and mortar of acute care facilities. In fact, research shows that an effective formalized transition of care program should not stop at discharge [7][8][9][10][11][12] . If the patient is discharged home and falls within the high risk of readmission category, then specific steps should be in place to help to ensure that the patient undergoes a safe transition of care back into the home.…”
Section: Buildingmentioning
confidence: 99%
“…The mean number of discrepancies per subject, between the hospital discharge list and home medications reported 48 hours later, was 2.02 [SD 1.8, range [1][2][3][4][5][6][7][8][9][10][11][12][13]. Health literacy was not associated with having a medication discrepancy in simple bivariate analysis; 65.9% subjects with low health literacy, 63.3% subjects with marginal health literacy, and 67.9% subjects with adequate health literacy experienced at least one medication discrepancy (p= 0.84).…”
Section: Medication Discrepanciesmentioning
confidence: 99%
“…Coleman et al found a total of 14.3% of the patients who experienced medication discrepancies were rehospitalized at 30 days compared with 6.1% of the patients who did not experience a discrepancy. 13 Adherence is the decision to follow the recommendations or treatment plan of the prescribing health care professionals.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these have been previously discussed and include patient safety, with high rates of medication errors, [17][18][19][20] incomplete or inaccurate information on transfer 75 and lack of appropriate follow-up care. 22 The transition coach will have addressed many of these issues; however, the frailty of this group of patients cannot be underestimated.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The reasons for these readmissions are multifactorial, but an important component is the availability of appropriate resources in the community that are able to respond to the needs of these patients in a responsive manner. Patient safety is often compromised during this vulnerable period, with high rates of medication errors, [17][18][19][20] incomplete or inaccurate information on transfer 21 and lack of appropriate follow-up of care 22 collectively leading to fragmented discharge planning and increased rates of recidivism to high-intensity care settings. 21 In England and Wales, to address the problem of rising readmission rates, the Department of Health has allocated £300M as part of the funding for reablement linked to hospital discharge funding stream [see www.gov.uk/government/uploads/system/uploads/attachment_data/file/215824/dh_123473.pdf (accessed 4 January 2016)].…”
Section: Chapter 2 Introductionmentioning
confidence: 99%